A mixture of postbiotics/tyndallized probiotics reduces trimethylamine (TMA) in trimethylaminuria models: Evidence from in vitro and in vivo studies - Giannini, Giuseppe; Soldi, Sara; Elli, Marina; Sagheddu, Valeria; Castagnetti, Andrea; Viciani, Elisa; Salvini, Laura; Battistuzzi, Gianfranco; Milazzo, Ferdinando Maria; Alibrandi, Simona; Sidoti, Antonina (Frontiers in Pharmacology, 2025)
IntroductionTrimethylaminuria (TMAU), also known as “fish-odor syndrome,” is a rare metabolic disorder characterized by a body malodor that smells like a decaying fish. This syndrome is caused by a FMO3 liver enzyme malfunction, leading to trimethylamine (TMA) accumulation. To date, there is no definitive therapeutic treatment but only palliative care for TMAU, such as a controlled diet, taking antibiotics, or using acidic soaps to capture sweat-released TMA.MethodsHere, we describe an innovative approach for the treatment of this disorder, where the use of postbiotics/tyndallized probiotics is able to effectively inhibit the bacterial TMA lyase present, thus preventing the formation of TMA. We obtained a preparation (a mixture of tyndallized probiotics and their postbiotics) that was derived from the fermentation of Lacticaseibacillus paracasei in the presence of garlic extract and senna leaf. This preparation was used in in vitro assays on human fecal slurry while monitoring the levels of TMA released over time, and it was also tested in vivo in both Mus musculus C57BL/6 (FMO3+/+) strain WT and C57BL/6-Fmo3em1Smoc (KO) mouse models to measure the trimethylamine N-oxide (TMAO) and TMA levels in the blood and urine, along with gut microbiota analysis in feces via next-generation sequencing (NGS).ResultsL. paracasei fermentation yielded 4.1 × 1012 CFU/g lyophilized powder. In vitro assays involving fecal slurries supplemented with the fermentation product demonstrated a reduction in TMA levels, and the NGS analysis revealed that Collinsella, Clostridium, and Streptococcus were the most common bacterial genera that produced TMA. The in vivo study showed a significant reduction in TMAO levels in C57BL/6(FMO3+/+) strain WT mouse models and in TMA levels in C57BL/6-Fmo3em1Smoc (KO) mouse models. In addition, bacteria belonging to the TMA-producing genera were still present after treatment with the tested compounds, excluding their bactericidal action. The postbiotics obtained may find a useful therapeutic application both in the prevention of cardiovascular events and as valid supports to reduce TMA production in TMAU patients.